2003
DOI: 10.1096/fj.02-1107fje
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal PTEN expression in portal hypertensive gastric mucosa: A key to impaired PI 3‐kinase/Akt activation and delayed injury healing?

Abstract: Phosphatase and tensin homologue deleted on chromosome ten (PTEN) is a dual-specificity phosphatase that has activity toward both phosphorylated peptides and phospholipids. PTEN inhibits activation of Akt, the downstream effector of PI 3-kinase, which is integral to cell proliferation, migration, survival, and angiogenesis essential for tissue injury healing. PTEN expression and activation during injury healing remain unexplored. Portal hypertensive (PHT) gastric mucosa has impaired injury healing, but the und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
21
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 45 publications
3
21
0
Order By: Relevance
“…In addition to the mouse system and human cells (MEFs, HT1080, 293T 20 ), consistent significant effects have been observed in other cells and tissues, [21][22][23][24][25] (Table 1). Moorehead et al 22 observed that Egr1 is induced by and required for IGF-II-dependent induction of PTEN in the mouse mammary gland, an effect that is absent in Egr1-null mice.…”
Section: Ptensupporting
confidence: 64%
“…In addition to the mouse system and human cells (MEFs, HT1080, 293T 20 ), consistent significant effects have been observed in other cells and tissues, [21][22][23][24][25] (Table 1). Moorehead et al 22 observed that Egr1 is induced by and required for IGF-II-dependent induction of PTEN in the mouse mammary gland, an effect that is absent in Egr1-null mice.…”
Section: Ptensupporting
confidence: 64%
“…Importantly, we have observed that PI3K/Akt signaling in primary human lung epithelia occurs subsequent to PTEN inhibition and without further addition of agonists. Consistent with these observations, others have reported similar effects in cardiomyocytes during ischemia-reperfusion (39), corneal and skin epithelia (76), and gastric mucosal cells (65). Although activation of the PI3K/Akt pathway plays a role in facilitating epithelial repair consequent to PTEN inhibition, PTEN is pleiotropic by virtue of multiple downstream pathways directly affected by its phosphatase activity, and the importance of these other pathways remains unclear.…”
mentioning
confidence: 58%
“…In portal hypertensive gastropathy (PHT), there is distorted microangioarchitecture and impaired angiogenesis in gastric mucosa in response to ethanol injury . Studies have demonstrated that PHT exhibits defects in signaling pathways such as Erk and PI3k/Akt and has overexpressed NOS resulting in high NO levels . Each of these abnormalities likely contributes to the impaired angiogenesis demonstrated as a consequence of PHT.…”
Section: Introductionmentioning
confidence: 99%